Pengaruh Celebrity Endorser, Citra Merek Dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Produk Skincare Azarine Di Shopee - Shinta Ulfa; Puti Embun Sari (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine the influence of Celebrity Endorser, Brand Image, and Consumer Trust on purchasing decisions for Azarine skincare products on Shopee. The data used are quantitative data obtained from questionnaires. The sampling technique used non-probability sampling with a total of 100 respondents. Data processing was carried out using SPSS 25 through validity, reliability, classical assumption tests, and multiple linear regression analysis. The results of the study indicate that partially, Celebrity Endorser has a positive but insignificant effect on purchasing decisions. Brand Image has a positive and significant effect on purchasing decisions. Consumer Trust also has a positive and significant effect on purchasing decisions. Simultaneously, these three variables influence purchasing decisions for Azarine skincare products on Shopee.